Illustrated catalogue and distribution of Leptodirini from Europe, the Caucasus, and the Near East (Coleoptera: Leiodidae) - Čeplík, Dávid (Zootaxa, 2026)
An illustrated catalogue of Leptodirini from Europe, the Caucasus, and the Near East is provided. Subterranean genera are arranged by regions and listed alphabetically rather than phylogenetically. A phylogenetic classification sensu Fresneda, Giachino, Salgado, Faille, Bourdeau, Cieslak & Ribera, 2024 is included for each genus and for the group as a whole at the end of this work, together with information on distribution and basic habitus morphology. The catalogue also includes notes on basal morphological traits of the genera and their bionomy. Distribution maps are provided for all genera included in this paper. The introduction familiarizes the reader with the fundamental aspects of subterranean Leptodirini.